Kazakhstan : Agricultural Insurance Feasibility Study, Volume 2. Annexes - World Bank (Washington, DC, 2014)
Agriculture is a very important socioeconomic sector in Kazakhstan. The Government of the Republic of Kazakhstan (GRK) introduced a national compulsory crop insurance scheme in 2005 in order to provide grain producers and other farmers with a minimum level of protection against catastrophic climatic events. The overall objective of the current study is to assist the GRK in improving the existing mandatory crop insurance program. The study aims to identify sustainable market-based alternatives to the current crop insurance system in Kazakhstan. In this regard, all of the options for improving the current system that were developed under this study are market based and take into account global experience and the best insurance and reinsurance industry practices for agricultural insurance. The study follows the principles established in the agriculture risk management framework developed by the World Bank. The study focuses mainly on spring wheat crop production in the principal growing regions of Kazakhstan. The study is set out in six chapters. Chapter one gives introduction and objectives of the study. Chapter two presents an overview of agricultural production systems and markets in Kazakhstan, followed by an assessment of the climatic hazards and other risks affecting spring wheat in the country s main crop areas. Chapter three reviews the structure and performance of the current mandatory crop insurance system in Kazakhstan and identifies a series of institutional, operational, technical, and financial drawbacks of the current system. Chapter four presents a phased strategy and a series of options and recommendations for the GRK to consider for the introduction of market based solutions that aim to strengthen the current scheme. Chapter five explores the opportunities for developing new crop insurance products in Kazakhstan, including prefeasibility analyses for area-yield index insurance (AYII), weather index insurance (WII), and named-peril hail insurance for selected rayons. Finally, chapter six deals with the challenges of tailoring crop insurance to the needs of lower-income smaller farmers.